2012
DOI: 10.1124/mol.112.080044
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Kalirin in the Response of Rat Medium Spiny Neurons to Cocaine

Abstract: Kalirin-7 (Kal7), the major kalirin isoform in adult brain, plays a key role in the formation of dendritic spines in hippocampal/ cortical neurons. Its role in the GABAergic medium spiny neurons (MSNs) of the nucleus accumbens (NAc) and striatum, the areas known to play a key role in the common reward pathway, is not as well understood. Although Kal7 expression in mouse NAc increased in response to cocaine, MSN dendritic spine density did not differ from that for the wild type in Kal7-null mice. Unlike wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…The ability of repeated cocaine exposure to increase spine density in NAc neurons requires the presence of Kal7 15 . Consistent with this, spine formation in cultures of rat medium spiny neurons is increased in response to expression of exogenous Kal7 82 . Perhaps more strikingly, Kal7 KO mice self-administer cocaine at a much higher rate than WT mice, and exhibit significantly elevated locomotor responses to injected cocaine 13, 15 .…”
Section: Resultssupporting
confidence: 72%
“…The ability of repeated cocaine exposure to increase spine density in NAc neurons requires the presence of Kal7 15 . Consistent with this, spine formation in cultures of rat medium spiny neurons is increased in response to expression of exogenous Kal7 82 . Perhaps more strikingly, Kal7 KO mice self-administer cocaine at a much higher rate than WT mice, and exhibit significantly elevated locomotor responses to injected cocaine 13, 15 .…”
Section: Resultssupporting
confidence: 72%
“…6A); statistics and actual levels of expression are provided in Table 1. Similar to prior analyses of Kal7 RNA and protein expression in rodents receiving experimenter administered cocaine (Kiraly et al, 2010b;Mains et al, 2011;Ma et al, 2012), analysis of Kal7 transcripts in Wt mice revealed an increase after cocaine self-administration, with no signal in Kal7 KO mice ( Fig. 6A; Table 1).…”
Section: Resultssupporting
confidence: 49%
“…Chronic cocaine exposure produces a wide variety of changes in gene expression, and Kalrn has been identified as a cocaineresponsive gene (Kiraly et al, 2010b;Mains et al, 2011;Ma et al, 2012). Kalrn is a large, alternatively spliced gene that yields multiple protein products (Kiraly et al, 2010a); Kal7 and DKal7 are absent in Kal7 KO mice, whereas expression of the larger isoforms, Kal9 and Kal12, is increased when the single exon unique to Kal7 and DKal7 is deleted (Ma et al, 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the SynCAM1 is required to maintain the increased density of spines on NAc MSNs induced by chronic cocaine in rodent models of addiction (Giza et al, 2013). Kalirin 7, one of the Rho-guanosine diphosphate/guanosine triphosphate exchange factors (Rho-GEFs) known to play an important role in spine morphogenesis, has also recently been recognized as an essential determinant of dendritic spine formation following chronic cocaine exposure (Kiraly et al, 2010; Mains et al, 2011; Ma et al, 2012). Other factors recently shown to affect spine density in the NAc of rats and mice after chronic cocaine exposure include DNA methylation, increases in actin cycling and activation of the nuclear factor kappa B (NFkappaB) (Russo et al, 2009; LaPlant et al, 2010; Toda et al, 2010).…”
Section: Is Mef2 the Common Regulator Of Striatal Spine Changes Inmentioning
confidence: 99%